2020
DOI: 10.1038/s41598-020-60252-7
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients, minerals, antioxidant pigments and phytochemicals, and antioxidant capacity of the leaves of stem amaranth

Abstract: We evaluated 17 genotypes of stem amaranth (Amaranthus lividus) in terms of dietary fiber, moisture, carbohydrates, fat, ash, gross energy, protein, minerals, phytopigments, total antioxidant capacity (TAC), vitamins, total flavonoids (TFC), total polyphenols (TPC) and their variations. Stem amaranth leaves have abundant dietary fiber, moisture, carbohydrates, and protein. We found significant amount of potassium, calcium, magnesium (9.61, 24.40, and 29.77 mg g −1 DW), iron, manganese, copper, zinc, (1131.98, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
91
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 116 publications
(117 citation statements)
references
References 36 publications
17
91
9
Order By: Relevance
“…In this study; we observed that A. hypochondriacus has abundant protein, carbohydrates, dietary fiber, and moisture. The moisture contents observed in A. hypochondriacus leaves was greater than our previous studies of red morph amaranth 35 , weedy amaranth 36 , green morph amaranth 37 , stem amaranth 38 , while the moisture contents of A. hypochondriacus leaves were corroborated with our previous studies of A. blitum 39 . In contrast, the protein contents observed in A. hypochondriacus leaves were greater than our previous studies of red morph amaranth 35 , A. viridis weedy amaranth 36 , green morph amaranth 37 , stem amaranth 38 , and A. blitum 39 , while the protein contents of A. hypochondriacus leaves were corroborated with our previous studies of A. spinosus weedy amaranth 36 .…”
supporting
confidence: 90%
“…In this study; we observed that A. hypochondriacus has abundant protein, carbohydrates, dietary fiber, and moisture. The moisture contents observed in A. hypochondriacus leaves was greater than our previous studies of red morph amaranth 35 , weedy amaranth 36 , green morph amaranth 37 , stem amaranth 38 , while the moisture contents of A. hypochondriacus leaves were corroborated with our previous studies of A. blitum 39 . In contrast, the protein contents observed in A. hypochondriacus leaves were greater than our previous studies of red morph amaranth 35 , A. viridis weedy amaranth 36 , green morph amaranth 37 , stem amaranth 38 , and A. blitum 39 , while the protein contents of A. hypochondriacus leaves were corroborated with our previous studies of A. spinosus weedy amaranth 36 .…”
supporting
confidence: 90%
“…The pro-vitamin A was estimated following our previously described method [ 7 , 14 ]. The fresh leaf samples (0.5 g each) were extracted with adding acetone (10 mL, 80%) followed by centrifugation for 3–4 min at 10,000 × g. A spectrophotometer was set at 510 nm and 480 nm, respectively to read the absorbance.…”
Section: Methodsmentioning
confidence: 99%
“…Vitamin C was estimated following our previously described method [ 14 , 42 ] by pre-incubation of samples using Dithiothreitol. Ascorbate reduced ferric ion to ferrous ion.…”
Section: Methodsmentioning
confidence: 99%
“…A few genera of Amaranthus are used as a traditional medicine for the remedy of viral, malarial, diabetic, bacterial, and helminthic diseases and as snake bite antidote 2-4 . Amaranth leaves and stems are good economic sources of carotenoids, proteins, including the essential amino acids methionine and lysine, dietary fiber and minerals, such as magnesium, calcium, potassium, copper, phosphorus, zinc, iron, and manganese [5][6][7][8][9][10][11][12][13][14][15][16] . Amaranth is also abundant in several pigments, such as carotenoids, chlorophylls, amaranthine, anthocyanins, betalains, betaxanthins, and betacyanins 17,18 and natural antioxidant phytochemicals, such as vitamin C, betacarotene, flavonoids, and phenolic acids 19,20 , that act as reactive oxygen species (ROS) scavengers in the human body 21,22 .…”
mentioning
confidence: 99%